Intranuclear localization of transcription factories and immunoglobulin heavy chain gene alleles during human B-cell maturation - Pichugin, A.V.; Iarovaia, O.V.; Sklyar, I.V.; Lacombe, G.; Razin, S.V.; Fest, T.; Lipinski, M.; Vassetzky, Y.S. (Вiopolymers and Cell, 2016)
Immunoglobulin heavy chain (IGH) gene locus is expressed monoallelically in human B cells. Aim. To study the role of nuclear organization in regulation of the IGH expression during B-cell differentiation. Methods. Immunofluorescence in situ hybridization on 3D-preserved nuclei (3D immuno-FISH). Results. Active RNA polymerase II (Pol II) molecules and the IGH locus were detected in the periphery of the nucleoli at some stages of B-cell differentiation. Conclusions. We observed significant changes in the pattern of distribution of RNA polymerase II in the nucleus during B-cell differentiation, but no preferential co-localization of the productive IGH allele with the transcription factories in the vicinity of the nucleolus and in the nucleoplasm was observed.